Language Fluency as a Factor in Machine Translation Comprehension - Aiken, Milam; Park, Mina; Lindblom, Tobin (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Machine translations have been used for nearly 50 years, and although accuracy steadily improves, results do not often attain the standard set for human interpretation. Some people can understand poor translations better than others, but little is known about why this is so. Â Here, we show that language fluency was not a major factor in the ability of a human reader to comprehend a passage of text translated by computer, but prior topic knowledge could be.